Determinants of Climate Change Disclosure in Carbon-Intensive Firms: Evidence from the GCC Region - Razan Albaqali; Hessa Al-Fadhel (Emerging Science Journal, 2026)
This study examines Climate Change Disclosure (CCD) among carbon-intensive firms in the Gulf Cooperation Council (GCC) region and identifies the key firm- and country-level factors shaping such disclosure. Using cross-sectional data from 212 listed firms operating in carbon-intensive sectors in 2022, the study employs a disclosure index tailored to the GCC context and conducts a content analysis of annual and sustainability reports to measure disclosure practices. The results reveal low disclosure levels and limited external assurance of the disclosed information. A multiple regression model is developed to assess the effect of financial attributes, governance characteristics, and national environmental performance on CCD. The results confirm that firm size, leverage, Global Reporting Initiative (GRI) adoption, the presence of sustainability or environmental committees, and countries’ Environmental Performance Index (EPI) scores significantly and positively influence CCD, whereas firm age, profitability, and board independence do not have a significant impact on disclosure. To the best of the authors’ knowledge, this study provides the first empirical evidence of CCD determinants in the GCC, a carbon-reliant region with limited scholarly attention, and introduces a disclosure index adapted to regional reporting practices. The insights provided by the study offer practical value for regulators and stakeholders aiming to advance corporate transparency and climate accountability.